The influence of the incentives in the organizational training of an air navigation company [La influencia de los incentivos en la capacitación organizacional de una empresa de navegación aérea] - Aranda Arrese, William Mario (2021)
ABSTRACT The purpose of this research is to explain the influence that incentives (provided to the employees of an air navigation services provider in Peru) have on the organizational training of this institution. The Civil Aviation Instruction Center (CIAC) of the Peruvian Corporation of Airports and Commercial Aviation (CORPAC S.A.) is responsible for the training, updating and specialization of the company’s personnel (approximately 1,500 workers at the national level); with the purpose of optimizing their competencies and thus the provision of air navigation services in the Peruvian State. Secondary sources were used for the validation of the hypotheses, obtained from the data of the Management of the Civil Aviation Instruction Center (CIAC) of the company, during the period 2009-2018. The SPSS statistical program (version 25) was used for hypothesis testing and the linear regression method was applied, since it was determined to be the most appropriate, according to the characteristics of this research work.